(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2026)
Government-funded, interest-free youth loan schemes are central to promoting entrepreneurship and economic inclusion in Tanzania’s informal sector, yet their broader empowerment shapes effects remain underexplored. This study examines how financial capital youth empowerment across economic, psychological, social, and political dimensions. Using a mixed-methods case study in Arusha City Council, the analysis draws on survey data from 118 youth entrepreneurs supplemented by focus group discussions and semi-structured interviews. The results indicate that although access to loans facilitated business start-ups and enhanced self-confidence, the sustainability of these enterprises was impeded by insufficient training, inadequate institutional follow-up, and restricted market linkages. Some participants gained social recognition, but entrenched gender and age hierarchies continued to restrict decision-making power and political participation. Overall, the findings underscore the need for integrated interventions that combine financial support with capacity-building, institutional accountability, and inclusive governance mechanisms.